Layanan Pendidkan Anak Berkebutuhan Khusus Dengan Gangguan atau Kelaianan Mental Emosional Di SDN 103/II Tanjung Agung - Lestari, Nanda; Lasmiawati, Lasmiawati; Andriani, Opi (Program Studi Pendidikan Vokasi Seni Kuliner, 2023)
The research aims to determine the characteristics, factors that cause disruption, approaches that can be taken to overcome, and educational service models for children with special needs with emotional and behavioral disorders. This research is motivated by a variety of cases that occur related to the limitations of education obtained by children with special needs, even some of the childrenexperience discriminatory treatment. The research method is descriptive with data collection techniques in the form of literature studies from various references relevant to the symptoms observed. The collected data were analyzed descriptively qualitatively so that variations in characteristics and models of educational services can be seen for children with special needs with emotional and behavioral disorders. The results showed that children with emotional and behavioral disorders have characteristics including intelligence and learning achievement, social and emotional characteristics and immature, withdrawalbehavior. The model of educational services for children with special needs with emotional and behavioral disorders can be divided into 3, segregation education services, integrated education services/integration, and inclusive education